STUDI BAHASA ARAB DALAM PENGUATAN STUDI ISLAM: PERSPEKTIF MAZHAB POSTSTUKTURALISME - Yahya, M (IAIN Bone, 2023)
The school of poststructuralism comes as a development of the school of structuralism by providing several criticisms and improvements in it. One form of criticism and improvement is the emphasis of the School of Poststructuralism on efforts to bridge text and context. In this process, the study of Arabic with all its components such as the study of phonetics/phonology, morphology, syntax, semantics, and others must be directed to understand how Islam can be understood in various Islamic literature which generally uses Arabic as the language of instruction. The study of Arabic in strengthening Islamic studies has a complex work dimension that is in line with Arabic as a language and the various components that underlie its development.Â Keywords: Arabic Studies, Islamic Studies, School of Poststructuralism